Administrative data and scientific evidence: a lesson from France – the safety of systemic treatment for psoriasis during the COVID‐19 pandemic. (2nd November 2021) - Cazzaniga, S.; Naldi, L.
Abstract : Linked Article:  Penso et al . Br J Dermatol 2022; 186 :59–68 .